The Effect of Absorptive Capability on Relationship between Total Quality Management and New Product Innovativeness of ISO 9001 International Quality Standard in the Industries Sector, Thailand - Sirivariskul, Nirusa (International Review of Management and Marketing, 2019)
Many scholars have suggested that total quality management (TQM) is an important key that pushes innovation. Literature examines the effect of absorptive capability as a mediator of the relationship between TQM and new product innovativeness. However, there are a few studies investigated these relationships. This results draws on the resource-based view theory to examine sixty-two ISO 9001 firms. The finding shows that TQM is positively related to new product innovativeness. More importantly, the result indicated that absorptive capability positively mediated the relationship between both variables. Implication of the finding is meaningful for both academies and management. Keywords: Total Quality Management, New Product Innovativeness, Absorptive Capability JEL Classifications: D2, L2 DOI: https://doi.org/10.32479/irmm.7276